Peran Masyarakat dalam Pendampingan Pendidikan Agama Islam Anak di Masa Wabah Covid-19 - Monica Farhana; Fiska Ilyasir (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2021)
This study explains about Community Participation in Assisting Islamic Religious Education Learning Activities at Home During the Covid-19 Pandemic for Elementary School Children Case Study in Puspo Hamlet, Pateken Wonoboyo Temanggung. This research uses descriptive qualitative method and phenomenological approach. The results showed that the role of the Puspo community included voluntarily helping children learn through the implementation of non-formal education, namely organizing study groups for children, participating in educating children through TPA/TPQ educational institutions, and playing a role in providing facilities and infrastructure for support learning activities.Â